Improving regional care in the last year of life by setting up a pragmatic evidence-based Plan–Do–Study–Act cycle: results from a cross-sectional survey - Lena Ansmann; Holger Pfaff; Ingrid Schubert; Ludwig Kuntz; Stephanie Stock; Sheila Payne; Nadine Scholten; Ute Karbach; Stefanie Hamacher; Raymond Voltz; Christian Albus; Frank Jessen; et al. (BMJ Open)
Objectives To set up a pragmatic Plan–Do–Study–Act cycle by analysing patient experiences and determinants of satisfaction with care in the last year of life.Design Cross-sectional postbereavement survey.Setting Regional health services research and development structure representing all health and social care providers involved in the last year of life in Cologne, a city with 1 million inhabitants in Germany.Participants 351 bereaved relatives of adult decedents, representative for age and gender, accidental and suspicious deaths excluded.Results For the majority (89%) of patients, home was the main place of care during their last year of life. Nevertheless, 91% of patients had at least one hospital admission and 42% died in hospital. Only 60% of informants reported that the decedent had been told that the disease was leading to death. Hospital physicians broke the news most often (58%), with their communication style often (30%) being rated as ‘not sensitive’. Informants indicated highly positive experiences with care provided by hospices (89% ‘good’) and specialist palliative home care teams (87% ‘good’). This proportion dropped to 41% for acute care hospitals, this rating being determined by the feeling of not being treated with respect and dignity (OR=23.80, 95% CI 7.503 to 75.498) and the impression that hospitals did not work well together with other services (OR=8.37, 95% CI 2.141 to 32.71).Conclusions Following those data, our regional priority for action now is improvement of care in acute hospitals, with two new projects starting, first, how to recognise and communicate a limited life span, and second, how to improve care during the dying phase. Results and further improvement projects will be discussed in a working group with the city of Cologne, and repeating this survey in 2 years will be able to measure regional achievements.Trial registration number DRKS00011925.